Analisis Yuridis Program Makanan Bergizi dalam Mendorong Pembangunan Nasional dan Pemenuhan Hak Gizi Anak Indonesia - Aura Kalisha; Parningotan Malau (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
The Free Nutritious Meal Program (MBG) is a strategic initiative by the Indonesian government to address the long-standing issues of malnutrition and stunting, which have significantly hindered human resource (HR) development in Indonesia. The program aims to improve children's nutrition and reduce stunting by providing free nutritious meals, particularly in areas with limited access to healthy food. This study aims to analyze the legal framework of MBG, its effectiveness in achieving its goals, and its impact on national development. Using a qualitative approach, the study analyzes the implementation of MBG through document analysis, interviews with relevant stakeholders, and field observations. The findings highlight challenges within the program, including imbalanced food distribution, inadequate infrastructure in remote areas, and suboptimal food quality control, which resulted in several food poisoning incidents in 2025. Nevertheless, the program has a positive economic impact by empowering micro, small, and medium enterprises (MSMEs) involved in food supply. The study suggests strengthening the monitoring system, improving budget management, and better coordination between government sectors and communities to maximize the success of MBG. It also emphasizes the importance of nutrition education campaigns to support the program's goals. Overall, MBG is a crucial step toward creating a healthier and more productive generation, supporting the achievement of Indonesia's Golden Generation by 2045..